Clinicoepidemiological study of prevalence and pattern of dermatoses among patients of pediatric age group in southeast region of Rajasthan - Shivani Saini; Devendra Yadav; Ramesh Kumar (Wolters Kluwer Medknow Publications, 2020)
Background: Pediatric dermatoses present as one of the most common clinical entities in dermatology clinics. They differ in clinical presentation and management from adults. Their prevalence and pattern differ from region to region due to several factors such as environmental, social, genetic, and cultural. Aims and Objective: The aim of the study was to determine the prevalence and pattern of various dermatoses among children of the age group 0-18 years in Southeast region of Rajasthan. Materials and Methods: Our study included 1000 cases of 0-18 years age group attending the dermatology outpatient and inpatient department of Government Medical College and attached group of hospitals, Kota. It was carried out from December 2017 to September 2018 (10 months). Appropriate history was taken, and a complete thorough examination was done as required. Relevant investigations were done, and all the findings were recorded in predesigned pro forma. Results: Our study included 560 males and 440 females of 1000 with the male-to-female ratio of 1.272:1. There were 553 urban and 447 rural participants. The patients were subgrouped in the age group of 0-1 year, 1-7 years, 8-12 years, and 13-18 years. The most prevalent dermatoses in 0-1 year age group were eczematous disorders (31.91%). Viral infections were predominant in 26.08% and 23.47% in the age groups of 1-7 years and 8-12 years, respectively. The most common dermatoses in the age group of 13-18 years were disorders of sweat and sebaceous glands (20.15%). Conclusion: Our study demonstrates variability of dermatoses among pediatric patients according to their age groups. This information should contribute to raising the awareness of pediatricians and dermatologists regarding the most common dermatological diagnosis in those patient populations.